The effect of overexpression of auxiliary Ca(2+) channel subunits on native Ca(2+) channel currents in undifferentiated mammalian NG108-15 cells - Wyatt, Christopher N (Blackwell Science Inc, 1998)
1. High voltage activated (HVA) Ca(2+) channels are composed of a pore-forming α1 subunit and the accessory β and α2–δ subunits. However, the subunit composition of low voltage activated (LVA), or T-type, Ca(2+) channels has yet to be elucidated. We have examined whether native calcium channels in NG108-15 mouse neuroblastoma × rat glioma hybrid cells, which express predominantly LVA currents when undifferentiated, are modulated by overexpression of accessory calcium channel subunits. 2. Endogenous α1A, B, C, D and E, and low levels of β and α2–δ subunit protein were demonstrated in undifferentiated NG108-15 cells. 3. The α2–δ, β2a or β1b accessory subunits were overexpressed by transfection of the cDNAs into these cells, and the effect examined on the endogenous Ca(2+) channel currents. Heterologous expression, particularly of α2–δ but also of β2a subunits clearly affected the profile of these currents. Both subunits induced a sustained component in the currents evoked by depolarizing voltages above −30 mV, and α2–δ additionally caused a depolarization in the voltage dependence of current activation, suggesting that it also affected the native T-type currents. In contrast, β1b overexpression had no effect on the endogenous Ca(2+) currents, despite immunocytochemical evidence for its expression in the transfected cells. 4. These results suggest that in NG108-15 cells, overexpression of the Ca(2+) channel accessory subunits α2–δ and β2a induce a sustained component of HVA current, and α2–δ also influences the voltage dependence of activation of the LVA current. It is possible that native T-type α1 subunits are not associated with β subunits.